A common TLR1 polymorphism is associated with higher parasitaemia in a Southeast Asian population with Plasmodium falciparum malaria. (December 2016) - Hahn, William; Harju-Baker, Susanna; Erdman, Laura; Krudsood, Srivicha; Kain, Kevin; Wurfel, Mark; Liles, Wayne
Abstract Background The factors leading to poor outcomes in malaria infection are incompletely understood. Common genetic variation exists in the human genes for Toll like receptors (TLRs) that alter host responses to pathogen-associated molecular patterns. Genetic variation inTLR1 andTLR6 could alter the risk of development of complicated malaria and ability of the host to control the parasite burden during acutePlasmodium falciparum infection. Methods Five single nucleotide polymorphisms inTLR1 andTLR6 in 432 patients with clinicalP. falciparum monoinfection acquired on the Thai-Myanmar border were genotyped. Using logistic regression, associations with the development of complicated malaria and the percentage of infected erythrocytes (parasitaemia) on the day of presentation to clinical care (day zero) were tested. Results Genotypes carrying the T (major) allele ofTLR1 rs5743551—an allele associated with improved outcomes in sepsis—were associated with higher parasitaemia measured on day zero (p = 0.03). Discussion Since malaria exerts strong genetic pressure on the human genome, protection from parasitaemia associated withTLR1 rs5743551 may account for the maintenance of an allele associated with poor outcomes in Caucasians with sepsis. Conclusion These data suggest that genetic variation inTLR1 has effects on the host response toPlasmodium falciparum malaria in Asian populations. Genotypes fromTLR6 showed no evidence of association with either complicated malaria or parasite burden.